KEANEKARAGAMAN JENIS IKAN DI SUNGAI DIGOEL DISTRIK EDERA KABUPATEN MAPPI - Robert S. Buhdy; Norce Mote; Edy HP. Melmambessy (Faculty of Agriculture Musamus University, 2018)
Fisheries production in the mainland waters of Mappi Regency is larger (27.48%) compared to marine fisheries (8.53%). Edera District is one of the districts in Mappi District which contributes to the potential of fisheries specifically for mainland waters. This study aims to determine the diversity of fish species in the Digoel River, Edera District, Mappi Regency. The fishing gear used is gill nets, stocking nets, fixed lines, fishing rods and spoon nets (tanggo). The study was conducted in August - October 2017 using the survey method. The variables analyzed were the species diversity index, evenness index, dominance index and relative abundance index. The results of the study obtained 28 species of fish which were divided into 8 orders of 20 families and 28 species. The value of the diversity of fish species is moderate, the Evenness value is relatively stable and evenly distributed, the type of dominance in Di shows that there is no dominance of species and the relative abundance of Kr is medium. Keywords: Digoel River; Diversity; Evenness; Dominance and Relative Abundance.